Aggregate Programming for the Internet of Things. - Beal, Jacob; Pianini, Danilo; Viroli, Mirko (Computer (00189162), 2015)
Through field calculus constructs and building-block APIs, aggregate programming could help unlock the IoT's true potential by allowing complex distributed services to be specified succinctly and by enabling such services to be safely encapsulated, modulated, and composed with one another.